C-Reactive Protein Levels in Male and Female Blood Donors at Kenyatta National Hospital, Kenya - Ireri, J. M. (Advances in Social Sciences Research Journal, 2022)
Background: C-reactive protein is an inflammatory marker and has found a wide clinical application in monitoring disease progress, effectiveness of treatment and post-operative complications. Determination of gender – based reference intervals of this protein would be of great value in eliminating any biases in results interpretation. It was in this endeavor that this cross-section study was conducted at Kenyatta National Hospital, blood donor unit, between 2018 and 2019. Objectives: To determine gender-based means, medians and 2.5 th and 97.5 th interquartile ranges of C-reactive protein (CRP) in suitable blood donors attended to at the blood donor unit of Kenyatta National Hospital, Kenya. Methods: A total of 108 (53.5%) female and 94 (46.5%) male volunteer blood donors aged between 18 and 60 years were recruited consecutively as they consented. Their social demographic characteristics were captured using a questionnaire form. Immediately after blood donation five milliliters of blood samples for CRP determination were drawn from the pilot tube of the blood bag by injecting the cap of an Ethylene dopamine tetra acetic acid (EDTA) vacutainer with the donation needle. Extracted plasma samples were stored frozen at -70 0 C till analysis. Analysis was done using standard laboratory methods. Statistical analyses were done using SPSS version 21. Bootstrap methods were used to calculate means, medians and confidence intervals. The fit of the observed data distribution was determined using Shapiro – Wilk tests with P > 0.05 indicating Gaussian distribution. Means, medians and 2.5 th and 97.5 th interquartiles were determined. Gender – based comparison of the medians were done using Wilcoxon rank-sum test with, p< 0.05, considered significant. Results: The male enrollees had a mean age of 31.91 years, while females’ mean age was 31.85 years. C-reactive protein demonstrated non-parametric distribution. Females’ medians were higher than males’ (11.7 mg/l vs. 4.4 mg/l, p< 0.01) Conclusion: The females have significantly higher CRP median values than males in health.